Additional observations of Spiniferites alaskensis from topotype material. (20th December 2018) - Marret, Fabienne; Mertens, Kenneth Neil
Abstract: Here we present new observations of Spiniferites alaskensis, a relatively rare species described from the Eemian of the Gulf of Alaska. We show that the species shows a gonyaulacacean tabulation: Po, 4´, 6´´, 6c, ? s, 6´´´, 1p, 1´´´´. The surface is finely granulate to scabrate. The species bears characteristic processes: these are exclusively gonal, membranous, perforated and end distally in platforms with stumpy ends. We provide more detail as how this species compares to closely related species belonging to the genus Spiniferites.